Selektifitas Transpor Lantanum Dari Mineral Monasit Dengan Teknik Supported Liquid Membrane - Djabal Nur Basir (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2009)
Transport selectivity of lanthanum from monazite mineral by supported liquid membrane, SLM technique has been studied. The supporting membrane, PTFE(polytetrafluoroethylene) was activated by immersing in a mixture of TBP(trybuthylphosphate) and D2EHPA (di-2-ethylhexyl phosphoric acid) at the composition of concentration in kerosene as carrier. Determination of the REE’s total concentration was carried out by visible spectrophotometric with NAS (sodium alizarin sulfonat) as the colouring agent, absorbance of the solution was determinated at 534 nm as maximum wavelength. For the determination of REE,s specific concentration an ICP-AES has been adopted, at emission maximum wavelength in each specific of REE’s, e.q : Ce at 418.66 nm, La at 408.316 nm, Nd at 401.225 nm, Gd at 342.247 nm, and Lu at 261.542 nm. Transport selectivity of lanthanum through SLM in a mixture of the REE’s simulation by optimum condition were pH of feed phase was 3.0, concentration of carrier composition (TBP : D2EHPA) was (0.3 : 0.7) M, and concentration of chloride acid of the receiving phase was 3.0 M. In this condition, separation factor of La toward Nd, Gd, and Lu : αLa,Nd 5.0297, αLa,Gd 8.1935, , αLu,La 11.9529. Transport selectivity of lanthanum from monazite mineral through SLM at optimum condition have been resulted lanthanum with the perity rate of increase from 25.08% to 89.84%, with recovery was 84.15%.Keywords : supported liquid membrane, carrier, polytetrafluoroethylene, trybuthylphosphate, di-2-ethylhexyl phosphoric acid.